Ontology in Public Administration Includes Potential, Positivism and Rationalism Approaches - Antonio Daniguelo (Journal La Sociale, 2020)
This paper discusses Public Administration Ontology departing from the fundamental understanding of administrative ontology, which is a thought based on the nature and meaning contained in administration itself as a branch of administrative science. The ontology basis of scientific development of public administration in the context of the philosophy of administrative science is the essence of what is studied from the aspect of how the public administration process is managed properly to regulate, serve and protect the public interest. So here the government bureaucracy and also non-governmental organizations that play a role in carrying out government functions, both in the implementation of public services and economic, social and other development fields collectively. Substantially the area of study for managers' work has a variety of interests from governance and public matters, from defense and security to social welfare and environmental quality, from road and bridge design and construction to space exploration and from tax and financial administration to management issues. human Resources. This paper also discusses the Administrative Ontology Approach, Positivism and Rationalism in Administration.